1991
DOI: 10.1073/pnas.88.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a single divalent cation directly correlates with the blue-to-purple transition in bacteriorhodopsin.

Abstract: We have characterized a unique divalent cation binding site on bacteriorhodopsin which controls the blue-to-purple transition in the purple membrane of Halobacterium halobium. To identify this site we first showed the correlation between the binding of one Ca2+ per bacteriorhodopsin and the amount of blue membrane converted to purple membrane. When the free Ca2+ was reduced below 1 pM, and the pH was set below 5.0 with 0.5 mM citrate, only binding to this high-affinity site was observed, and we could separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 26 publications
8
84
0
Order By: Relevance
“…They suggested that this value was too high (especially at pH 1) and was probably due to complications from protein conformational changes. Jonas and Ebrey (1990) have repeated Kimura et al's experiment, mostly at higher salt concentrations, and their results suggest a higher intrinsic pK, (ca 2) and a much lower surface charge density, from less than 1, to 3 charges per 1140 A' . A constant surface charge density could not be obtained from this data at the different ionic strengths.…”
Section: Measurements Of the Surface Potential And Surface Charge Denmentioning
confidence: 93%
See 3 more Smart Citations
“…They suggested that this value was too high (especially at pH 1) and was probably due to complications from protein conformational changes. Jonas and Ebrey (1990) have repeated Kimura et al's experiment, mostly at higher salt concentrations, and their results suggest a higher intrinsic pK, (ca 2) and a much lower surface charge density, from less than 1, to 3 charges per 1140 A' . A constant surface charge density could not be obtained from this data at the different ionic strengths.…”
Section: Measurements Of the Surface Potential And Surface Charge Denmentioning
confidence: 93%
“…Those experimental results which are probably specific for the N-terminal, extracellular side of the membrane are mostly between 1 and 4 negative charges per bR. At low pH, the acid-induced purple-to-blue transition as a function of the ionic strength suggests surface charge densities ranging from less than 1, to 3 negative charges per bR at pH 2 (Jonas and Ebrey, 1990). At pH 7.5, Ehrenberg et al (1989) found 2 negative charges per bR.…”
Section: Measurements Of the Surface Potential And Surface Charge Denmentioning
confidence: 98%
See 2 more Smart Citations
“…More recent work by Ebrey etal. [24] on the correlation of color change and the number of Ca ~+ ions bound and the H + ions produced, strongly suggested the importance of one calcium ion in bR. From the recently proposed model for the structure of bR [25], Ebrey suggested that tt~is Ca a+ ion might be located within the retinal pocket [24].…”
Section: Introductionmentioning
confidence: 99%